Responses to water stress extremes in diverse red clover germplasm accessions - Heslop, Angus D.; Jahufer, Zulfi; Hofmann, Rainer W. (Frontiers in Plant Science, 2023)
Red clover (Trifolium pratense L.), a key perennial pastoral species used globally, can strengthen pastural mixes to withstand increasingly disruptive weather patterns from climate change. Breeding selections can be refined for this purpose by obtaining an in-depth understanding of key functional traits. A replicated randomized complete block glasshouse pot trial was used to observe trait responses critical to plant performance under control (15% VMC), water deficit (5% VMC) and waterlogged conditions (50% VMC) in seven red clover populations and compared against white clover. Twelve morphological and physiological traits were identified as key contributors to the different plant coping mechanisms displayed. Under water deficit, the levels of all aboveground morphological traits decreased, highlighted by a 41% decrease in total dry matter and 50% decreases in both leaf number and leaf thickness compared to the control treatment. An increase in root to shoot ratio indicated a shift to prioritizing root maintenance by sacrificing shoot growth, a trait attributed to plant water deficit tolerance. Under waterlogging, a reduction in photosynthetic activity among red clover populations reduced several morphological traits including a 30% decrease in root dry mass and total dry matter, and a 34% decrease in leaf number. The importance of root morphology for waterlogging was highlighted with low performance of red clover: there was an 83% decrease in root dry mass compared to white clover which was able to maintain root dry mass and therefore plant performance. This study highlights the importance of germplasm evaluation across water stress extremes to identify traits for future breeding programs.